Evgenyi Sadovyi's Full Stroke at 120 m of His Gold Medal 400 m Race at the Barcelona Olympic Games 1992 - Rushall, B. S.
Video pictures (17 frames) and the appropriate technical/ biomechanical explanations for Evgenyi Sadovyi's full stroke at 120 m of his gold medal 400 m race at the Barcelona Olympic Games 1992. In Sadovyi's arm movements there is a distinct absence of any "S-shaped" arm pull pattern. There is little commonality between the left and right arm pull patterns. It would be misleading to claim that Sadovyi demonstrates a particular stroking pattern as each arm pull is distinct. The asymmetry of the arm movements is characteristic of that exhibited by most champion crawl stroke swimmers. The arm entry appears to be an unimportant aspect of the stroke. Both arms enter elbow first almost at a complete stretch. Sadovyi's stroke appears to be relatively "rough." His hips bob up and down (frames #6 and #7) and the head is raised up and down (frame #5), features which should increase resistance. There are brief time periods in Sadovyi's stroke where no propulsive forces seem to be generated.